2012
DOI: 10.1021/ac202816y
|View full text |Cite
|
Sign up to set email alerts
|

Linear Ion Trap MSn of Enzymatically Synthesized 13C-Labeled Fructans Revealing Differentiating Fragmentation Patterns of β (1-2) and β (1-6) Fructans and Providing a Tool for Oligosaccharide Identification in Complex Mixtures

Abstract: Fructans are polymeric carbohydrates, which play important roles as plant reserve carbohydrates and stress protectants, and are beneficial for human health and animal production. Fructans are formed by the addition of β-d-fructofuranosyl units to sucrose, leading to very complex mixtures of 1-kestose based inulins, 6-kestose linked levans, and 6G-kestose derived neoseries inulins and levans in cool season grasses such as Lolium perenne. The identification of isomeric fructan oligomers in chromatographic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 28 publications
3
26
0
Order By: Relevance
“…Data were collected in centroid mode and analyzed with Xcalibur 3.0 software. Carbohydrates were identified by injection of commercial available standards and enzymatically synthesized fructan standards (Verspreet et al, 2014b) and by comparison of the MS 2 spectra with earlier published data (Harrison, 2012;Harrison et al, 2012). The nomenclature of Domon and Costello (1988) was used for the designation of the fructan fragments formed.…”
Section: Liquid Chromatography-mass Spectrometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Data were collected in centroid mode and analyzed with Xcalibur 3.0 software. Carbohydrates were identified by injection of commercial available standards and enzymatically synthesized fructan standards (Verspreet et al, 2014b) and by comparison of the MS 2 spectra with earlier published data (Harrison, 2012;Harrison et al, 2012). The nomenclature of Domon and Costello (1988) was used for the designation of the fructan fragments formed.…”
Section: Liquid Chromatography-mass Spectrometrymentioning
confidence: 99%
“…LC-MS combines the separating power of liquid chromatography and the structural characterization capacity of mass spectrometry. This allows the detection and characterization of individual fructan oligosaccharides in complex fructan mixtures (Harrison et al, 2012), such as found in wheat grain extracts. Wheat grain fructan structure is investigated in different grain tissues because grain tissues are often separated during wheat processing.…”
Section: Introductionmentioning
confidence: 99%
“…4(b)) comprises a X 2 ** fragment ion (m/z 395) corresponding to a cross-ring cleavage product containing two labeled fructose units that were β(2,6)-linked to the initial fructan structure. [17] Only 1&6,6-KP (m/z 839) and 1,6,6-KP (m/z 839) can form this fragment, but the absence of the 677 fragment indicates that this is the MS 2 spectrum of 1,6,6-KP. Further evidence for the identity of these structures was found in the HCD spectra.…”
Section: Fragmentation Of Dp 5 Fructansmentioning
confidence: 99%
“…2), as previously seen for inulin-and levan-type fructans. [17] Comparison of the MS 2 spectra of native 1&6-KT ( Fig. 2(a)) and [UL-13 C 6 fru] 1&6-KT ( Fig.…”
Section: Enzymatic Synthesis Of Branched Fructansmentioning
confidence: 99%
“…These advantages lead to a significant improvement of analytical performance such as sensitivity and dynamic range. Owing to its good performance and capability of tandem mass spectrometry, the linear ion trap mass spectrometer has been commercialized and used in many fields [4][5][6][7].…”
mentioning
confidence: 99%